Transmissão intergeracional de práticas relativas a estudo em famílias com estudantes no ensino básico - Cunha, Renan Soares Mendes Teixeira da (2012)
Children socialization development is influenced by their parents through parental style and practices. Parents can assume the function of promoting agents of study behavior of their children through parental practices. Results of training programs directed to parents as study supervisors show that they have difficulties to behave more accordingly to supervision practices which the literature accepts as more adequate. An explicative hypothesis for that is that parents learned to supervise their children according to the conditions and models their parents used with them. This possibility can be illustrative of a situation of intergenerational transmission of parental practices relating to studying situation. Articulating with concepts of the Behavior Analysis, this research objective was to investigate which are the possible relations between the conditions created for the development of parents´ study repertory and the conditions created by parents to the development of their children study repertory. Participants of this research where representatives of three generations maternal grandmother, mother and child studying at the fundamental grades of public schools, of five families. Grandmothers were aged between 53 and 69 and had scholar degree between none and third grade of supplementary high school; mothers were aged between 33 and 41 and had scholar degree between second grade of fundamental school and post-graduation at a specialization level; children were aged between 9 and 13 and had scholar degree between third grade/fourth year and sixth grade/seventh year of fundamental school. Data were accessed through semi-structured interviews, taken individually and separately with each participant, at their residences or workplaces. The interviews were recorded, when agreed, or written down, when not agreed. All of the participants signed TCLEs. The research was approved by the Ethic Committee of UFSCar. The method of data analysis consisted in categorizing the collected information, grouping them into variables which influence studying (local of study, time of study, supervisor´s responses to mistakes and hits, etc.). Using the synthesis of the reports of the dyad mother-child related to the conditions focusing the child and of the reports of the dyad grandmother-mother related to past study conditions focusing the mother when she was a student, comparative frameworks were built, indicating which variables or variable values were similar or different between the three generations and, when it was possible, which kind of similarity. Finally, frameworks were built with synthesis of identifyed aspects, indicating intergenerational continuities and discontinuities to each family. Results showed that for Family 1, about the dyad grandmother-mother there was continuity for six variable values and discontinuity for four, about the dyad motherchild there was continuity for thirteen values and discontinuity for two; for Family 2, about the dyad grandmother-mother there was continuity for one variable value and no discontinuity, about the dyad mother-child there was continuity for six values and discontinuity for two; for Family 3, about the dyad grandmother-mother there was no continuity for one value and no discontinuity, about the dyad motherchild there was continuity for eleven values and discontinuity for eight; for Family 4, about the dyad grandmother-mother there was continuity for four variable values and discontinuity for one, about the dyad mother-child there was continuity for eight values and discontinuity for three. ; for Family 5, about the dyad grandmother mother there was continuity for five values and discontinuity for another five, about the dyad mother child there was continuity for eight values and discontinuity for seven. It was vereified a strong tendency of intergenerational continuity of responses, behaviors and conditions related to the study, accordingly to the initial hypothesis. Through the data it was possible to discuss which aspects of children study parents observe, value and consequence. Results can subside future training programs directed to parents as favoring of their children study behaviors.